Results of the Sawanpracharak Newborn Hearing Screening Program - Chareonsil, Rungjai (Biomedical Sciences and Clinical Medicine, 2024)
Objective To determine the prevalence of congenital hearing loss and evaluate the benefit of the Sawanpracharak Newborn Hearing Screening Program. Materials and methods A prospective descriptive study of congenital hearing loss was carried out in 2,773 newborns using the Sawanpracharak Newborn Hearing Screening Program between January 2012 and March 2013. The results were based on the 2-screening test and transient-evoked otoacoustic emission test (TEOAE) at <1 month and 3 months of age, and the newborn participants were divided into two groups, “pass” and “refer”. Newborns who failed the second screening test (“refer”) were assessed for hearing threshold, with auditory brainstem response (ABR) at 6 months of age. Results Two hundred and eleven of 2,773 (7.6%) newborns failed the fi rst TEOAE and 63 of 1,831 (3.4%) failed the second, with 942 newborns lost to follow-up for the second screening. Fifty-one of the 63 newborns (81%) were assessed for hearing loss with ABR (12 newborns were lost to assessment). Finally, four and three newborns had bilateral and unilateral hearing loss, respectively. All of them were at high risk of hearing impairment. Conclusion The prevalence of congenital hearing loss was 2.5:1,000 and screening with 2-TEOAE decreased missing “refer” cases that need confirmation of hearing status with ABR.